Proceedings of the 2014 Conference on Innovation &Amp; Technology in Computer Science Education - ITiCSE '14 2014
DOI: 10.1145/2591708.2591755
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of the acceptability of various code-writing practices

Abstract: This paper reports on research that used focus groups and a national online survey of computing students at Australian universities to investigate perceptions of acceptable academic practices in writing program code for assessment. The results indicate that computing students lack a comprehensive understanding of what constitutes acceptable academic practice with regard to writing program code. They are not clear on the need to reference code taken from other sources, or on how to do so. Where code from other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The major works addressing specifically attribution and plagiarism of non-text works acknowledge the lack of literature on the topic, while also arguing that it has not been addressed adequately within universities via formal academic honesty or academic integrity policies (Blythman et al, 2007;Garrett & Robinson, 2012;Simon, 2016;Simon et al, 2014). In research published in 2014, Simon et al conducted a survey of Australian academics and students who use non-text based assessments, and found 'a widespread perception … that current academic integrity policies in relation to non-text-based assessments, and associated efforts to educate students about these policies, are inadequate' (2014, p.13).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The major works addressing specifically attribution and plagiarism of non-text works acknowledge the lack of literature on the topic, while also arguing that it has not been addressed adequately within universities via formal academic honesty or academic integrity policies (Blythman et al, 2007;Garrett & Robinson, 2012;Simon, 2016;Simon et al, 2014). In research published in 2014, Simon et al conducted a survey of Australian academics and students who use non-text based assessments, and found 'a widespread perception … that current academic integrity policies in relation to non-text-based assessments, and associated efforts to educate students about these policies, are inadequate' (2014, p.13).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a subsequent survey of computing students and academics, they found substantial differences between the attitudes to certain practices with text and computing assessments and between perceptions of plagiarism/collusion and perceptions of acceptability (Simon et al 2014a). They also found that computing students have a poor understanding of acceptable academic practice when writing computer code, that they are not aware of the need to reference code taken from other sources, and that they do not know how to do so (Simon et al 2014b).…”
Section: Perceptions Of Academic Integrity In Computingmentioning
confidence: 99%
“…One clear finding from the literature is that many students and academics see no problem with students reusing code that they have written for another project [6,10,16], although outside computing education this is called self-plagiarism and is considered academically inappropriate [3].…”
Section: Academic Integritymentioning
confidence: 99%
“…There is also a widely held view that there is nothing wrong with students working together on individual assignments, or copying much of another student's assignment, so long as the student submitting the assignment does a reasonable amount of the work [6,10,16]. Again, in the broader world of academic integrity these practices are considered inappropriate, and are generally called collusion [3].…”
Section: Academic Integritymentioning
confidence: 99%
See 1 more Smart Citation